2000
DOI: 10.1038/sj.cdd.4400725
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of granzyme B-mediated cell death on a pathway regulated by Bcl-2 or its viral homolog, BHRF1

Abstract: The molecular pathways responsible for apoptosis in response to granzyme B have remained unresolved. Here we present data supporting the notion that granzyme Bmediated cell death is largely dependent on a pathway that is inhibitable by Bcl-2 or its viral analog BHRF1. We used a panel of stably transfected FDC-P1 mouse myeloid cell lines to show that overexpression of functional, wild-type Bcl-2 or BHRF1 rescued cells from granzyme B-mediated apoptosis, whereas mutated (Gly 145 ?Glu) Bcl-2, or wild-type Bcl-2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
41
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 49 publications
5
41
1
Order By: Relevance
“…On this basis, it was proposed that mitochondria are more appropriately seen as an amplification loop in the pathway to granzyme B-mediated apoptosis. These data challenge the hypothesis that Bid is required for granzyme B-induced cell death (16,17) and is inconsistent with studies that have shown a role for mitochondria in this pathway (1)(2)(3).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…On this basis, it was proposed that mitochondria are more appropriately seen as an amplification loop in the pathway to granzyme B-mediated apoptosis. These data challenge the hypothesis that Bid is required for granzyme B-induced cell death (16,17) and is inconsistent with studies that have shown a role for mitochondria in this pathway (1)(2)(3).…”
Section: Discussioncontrasting
confidence: 55%
“…These studies cumulatively suggested that neither Bid nor MOMP is required for granzyme B-mediated cell death and proposed that MOMP acts as an amplification loop that may be dispensable during granzyme B-induced apoptosis. Although these studies propose to provide insight into the molecular mechanism of granzyme B-induced cell death, they are inconsistent with a number of studies showing that cells overexpressing Bcl-2 are protected against granzyme B-induced apoptosis (1-3) and maintain their proliferative potential following exposure to cytotoxic concentrations of granzyme B (2,3).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…EBV encodes a viral homolog of BCL-2, anti-apoptotic BHRF-1, 10 which has conserved BH1 and BH2 domains homologous to BCL-2. 11 BHRF-1 can inhibit apoptosis induced by a number of death insults including serum depletion, 12 death induced by tumor necrosis factor a and anti-Fas antibody, 13,14 g irradiation, chemotherapeutic drugs, 15,16 deregulated c-myc, 17 granzyme B, 18 Sindbis virus infection 19 and the tumor suppressor protein p53. 20 BHRF-1 is expressed during the productive/lytic replication cycle.…”
mentioning
confidence: 99%